(untitled) (The Review of Diabetic Studies, 2025)
Background: Burnout is a major occupational health concern in modern healthcare systems, characterised by emotional exhaustion, depersonalisation, and reduced personal accomplishment. While numerous studies have examined burnout among physicians and nurses, limited research has focused on the broader multidisciplinary workforce, including health administrators, informatics professionals, pharmacists, dental practitioners, EMS personnel, and health assistant nurses. Aim: This systematic review aimed to synthesise evidence on the prevalence, contributing factors, and mitigation strategies for burnout and job satisfaction across diverse healthcare disciplines. Methods: Following the PRISMA 2020 guidelines, a systematic search was conducted in PubMed, Scopus, CINAHL, PsycINFO, and Web of Science for studies published between 2000 and 2025. Eligible studies reported data on burnout prevalence, risk factors, or interventions among multidisciplinary healthcare professionals. The Maslach Burnout Inventory (MBI) and Copenhagen Burnout Inventory (CBI) were the primary tools used. Data were synthesised narratively due to heterogeneity in study designs. Results: A total of 62 studies met the inclusion criteria. Overall burnout prevalence ranged from 38% to 57% across disciplines. The highest rates were found among EMS personnel (50–70%) and pharmacists (45–60%), followed by health assistant nurses (40–65%) and administrators (42–55%). Contributing factors included workload, administrative burden, digital fatigue, shift irregularity, and lack of organisational support. Effective interventions targeted leadership development, staff recognition, digital workflow optimisation, and peer-support programs. Conclusion: Burnout in healthcare is a multifactorial and multidisciplinary challenge that demands system-level solutions. Sustainable prevention requires organisational reform, digital health redesign, and psychological support structures integrated across professions. Embedding well-being indicators within hospital accreditation and health policy frameworks is essential to achieve workforce sustainability and align with the Quadruple Aim of healthcare — improving patient outcomes, reducing costs, enhancing population health, and preserving staff well-being.